2022
DOI: 10.1007/s00405-022-07561-x
|View full text |Cite
|
Sign up to set email alerts
|

Need for adjuvant radiotherapy in oral cancer: depth of invasion rather than tumor diameter

Abstract: Purpose The 8th edition of the TNM Cancer Staging Manual incorporates depth of invasion (DOI) into the pathologic tumor classification for oral squamous cell carcinoma (OSSC). While deep invading tumors with small tumor diameters (TD) have been categorized as early stage tumors in the 7th edition, they are now upstaged, potentially influencing the decision to initiate adjuvant radiotherapy (RT). Methods OSCC patients surgically treated with curative intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Treatment of OSCC remains mainly surgical, depending on the anatomic site, with adjuvant radiotherapy added for advancedstage disease. 21 The patient, in this case, underwent hemiglossectomy surgery on the right side of the tongue with the keyhole method followed by chemotherapy; it should be the optimal surgery for the early cancer stage. The selection of appropriate treatment modalities depends on tumor factors such as size (T-stage), location and multiplicity, proximity to the bone, pathological features, histology grade, and depth of invasion.…”
Section: Discussionmentioning
confidence: 94%
“…Treatment of OSCC remains mainly surgical, depending on the anatomic site, with adjuvant radiotherapy added for advancedstage disease. 21 The patient, in this case, underwent hemiglossectomy surgery on the right side of the tongue with the keyhole method followed by chemotherapy; it should be the optimal surgery for the early cancer stage. The selection of appropriate treatment modalities depends on tumor factors such as size (T-stage), location and multiplicity, proximity to the bone, pathological features, histology grade, and depth of invasion.…”
Section: Discussionmentioning
confidence: 94%
“…Larson et al ( 27 ) reported the rate of occult cervical metastases was very low when DOI was ≤4 mm in small (≤2 cm) tongue cancer, despite the existence of unfavorable perineural invasion and lymphovascular invasion. Other researchers ( 28 - 30 ), including the authors of this study, still use 5 mm as the category criterion, and obtain favorable hazard discrimination and prediction capabilities. Such phenomenon may result from the different cohort sources and incorporated factors, and more evidence-based research is required.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, DOI values vary from 1.5 to 10 mm in different studies. Thus, a mean value of 4 mm was taken as significant, and it represents an absolute indication for performing selective neck dissections 25 . The results of our study show a correlation between DOI and the presence of metastases in the lymph nodes of neck dissection specimens.…”
Section: Discussionmentioning
confidence: 99%
“…24 prikazuju rezultate kojima se dokazuje da je DOI najpouzdaniji prognostički parametar OPK-a u stadijumu T1-T2. Granična vrednost DOI u literaturi varira od 1,5 mm do 10 mm u različitim studijama, tako da je za signifikantnu srednju vrenost preuzeta vrednost od 4 mm, koja predstavlja apsolutnu indikaciju za sprovođenje selektivnih disekscija vrata 25 . Rezultati naše studije pokazuju korelaciju između DOI i prisustva metastaza u limfnim nodusima disekata vrata.…”
Section: Diskusijaunclassified